Percepción del cuidado de enfermería para el familiar cuidador de pacientes pediátricos - Alfaro Murga, Liliana Mercedes (2019)
Qualitative research had as objective to study the perception of the family caregiver of pediatric patients about nursing care. The theoretical approach is based on concepts: perception, care, nursing care, pediatric patients and hospitalization, according to the perspective of several authors. Its objectives were describe and understand the perception of nursing care for the family caregiver of pediatric patients. It used descriptive exploratory method with application of depth interviews to 10 participants. When analyzing the discourses, four categories were obtained with their respective subcategories: 1) Work overload: a) Work overload and b) Attention by practitioners; 2) De-humanized care: a) Commitment and un-concern, b) Care with affect and love, c) Spiritual care and inculcation of faith and d) Abuse of the child and the family; 3) Instrumental care: a) Medicine administration and b) Nursing procedure and 4) Therapeutic communication: a) Teaching / learning promotion, b) Communication and information with the family and c) Therapeutic game.